2017
DOI: 10.22161/ijeab/2.4.48
|View full text |Cite
|
Sign up to set email alerts
|

Removal from wastewater and recycling of azo textile dyes by alginate-chitosan beads

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Chitosan has great potential for environmental applications [6], such as the remediation of organic and inorganic contaminants, including toxic metals and dyes in soil, sediment, and water [7,8,9,10], and for the development of devices [11,12]. Among pollutants [13,14], emerging contaminants, e.g., pesticides and their metabolites, pharmaceuticals, personal and house care products, life-style compounds, food additives, industrial products and waste, and nanomaterials, are a great and important problem for the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan has great potential for environmental applications [6], such as the remediation of organic and inorganic contaminants, including toxic metals and dyes in soil, sediment, and water [7,8,9,10], and for the development of devices [11,12]. Among pollutants [13,14], emerging contaminants, e.g., pesticides and their metabolites, pharmaceuticals, personal and house care products, life-style compounds, food additives, industrial products and waste, and nanomaterials, are a great and important problem for the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the scientific community suggests different biodegradable and effective low‐cost adsorbent materials obtainable from natural resources. Among them, hybrid polymeric adsorbents are the most used for this application since several years …”
Section: Introductionmentioning
confidence: 99%
“…In Figure 6a and b are presented the effect of adsorbent dosage on β-CD/EPI and γ-CD/EPI polymers, respectively. It is possible to observe that both polymers have the same behaviour: the percentage of dye removal increased with the increase in dosage of polymers, due to the major availability of adsorbent surface sites [18]. In presence of β-CD/EPI polymer (Figure 6a), the removal of dye from the initial solutions increased from 41.20 to 98.90% as the adsorbent dosage increased from 0.05 to 1.00 g. When γ-CD/EPI polymer (Figure 6b) was used as an adsorbent, the removal of DB78 increased from 52.01 to 97.25% as the adsorbent dosage increased from 0.05 to 1.00 g. A further increase in dosage of polymers (1.25 g) did not improve the removal of both dye since the systems were achieved the maximum adsorption efficiency.…”
Section: Effect Of Adsorbent Dosagementioning
confidence: 92%
“…Attributable to their numerous and specific properties, CDs are widely employed in several areas such as pharmaceutical, biomedical, biotechnological, and industrial sectors [22,23]. Several studies also reported that CDs and CD-based materials are used in removal of dyes [18,19], organic pollutants, and heavy metals from water, soil, and atmosphere [23,24]. Moreover, in a previous study [25], the interaction between some azo textile dyes and some commercial cyclodextrins was already demonstrated.…”
Section: Cyclodextrinsmentioning
confidence: 94%
See 1 more Smart Citation